SOSIALISASI PERAN PENTING LEMBAGA BANTUAN HUKUM (LBH) SEBAGAI ACCESS TO JUSTICE BAGI MASYARAKAT TIDAK MAMPU DI DESA CAU BELAYU KECAMATAN MARGA KABUPATEN TABANAN - I.P.R.A. Putra; I.G. Artha; N.N. Adiyaryani; I.D.G.D. Sugama; N.K.R. Puspasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This community service activity has the aim of providing knowledge to the public about the existence of legal aid institutions as Access to Justice for people who can't afford it. The existence of legal aid institutions is intended for people who are unable to obtain their rights in facing legal problems both in court and outside the court. This activity was carried out in addition to providing an understanding of the existence of legal aid institutions as Access to Justice as well as socializing Law Number 16 of 2011 concerning Legal Aid. This activity is expected to be able to increase public understanding that disadvantaged people are also given access to achieving justice before the law. This community service uses fild research to find out the situation that occurs in the community, then uses library research to find devotional materials related to the important role of legal aid institutions as Access to Justice for the poor. In delivering the material using socialization and lecture methods delivered in an interactive, active and reflective way. The results of this activity are increasing public understanding of the existence of legal aid institutions as Access to Justice, increasing public knowledge regarding the requirements for resolving legal issues with the help of legal aid institutions and the existence of public knowledge of the mechanisms for resolving legal disputes with the assistance of legal aid institutions. Keywords: Legal Aid, Access to Justice, The Community Can’t Afford